Knowledge, Attitudes, and Stigma Related to Dementia Among Illiterate and Literate Older Adults in Shanghai - Yang T; Huang Y; Li X; Li M; Ma S; Xuan G; Jiang Y; Sun S; Yang Y; Wu Z; Li X; Wang Y (Dove Medical Press, 2021)
Tingting Yang,1,* Yanyan Huang,2,3,* Xinghui Li,1 Mengying Li,1 Suisui Ma,4 Guo Xuan,5 Yihua Jiang,5 Shuangyuan Sun,6 Yinghua Yang,7 Zhuochun Wu,1 Xiangyun Li,2 Ying Wang1,8 1School of Public Health, Fudan University, Shanghai, People’s Republic of China; 2Department of Geriatrics, Huashan Hospital, Fudan University, Shanghai, People’s Republic of China; 3Tian Qiao and Chrissy Chen Institute Clinic Translational Research Center, Shanghai, People’s Republic of China; 4Yuluo Management Consultation Co. Ltd of Shanghai, Shanghai, People’s Republic of China; 5Medicine-Mental Health Center of Minhang District/Minhang Branch, School of Public Health, Fudan University, Shanghai, People’s Republic of China; 6Shanghai Municipal Center for Disease Control and Prevention, Shanghai, People’s Republic of China; 7Shanghai Center for Clinical Laboratory, Shanghai, People’s Republic of China; 8Key Laboratory of Health Technology Assessment, National Health and Family Planning Commission of the People’s Republic of China, Fudan University, Shanghai, People’s Republic of China*These authors contributed equally to this workCorrespondence: Ying Wang Email wangying1013@fudan.edu.cnXiangyun Li Email ccwlxy.cool@163.comBackground: China has the largest population of patients with dementia worldwide, no assessment of illiterate old population’s dementia knowledge, attitudes, stigma have been conducted so far in China.Aim: This study focused on the impact of education on knowledge, attitudes, and stigma related to dementia.Methods: The community-based sample used in this study was recruited using multi-stage random sampling from residents aged ≥ 60 years registered in Shanghai. We used the Geriatric Depression Scale (GDS-30) to identify depression, and the Ascertain Dementia 8 questionnaire (AD8) for evaluating participants’ cognitive impairment. Knowledge, Attitude, Belief, and Practice scale, Perceptions Regarding Investigational Screening for Memory in Primary Care (PRISM-PC) were used for measuring dementia knowledge, attitudes, stigma. We separated the population into illiterate and literate group, propensity score matching based on age, sex, depression, and cognitive impairment. We calculated the difference of knowledge, attitudes, and stigma related to dementia between illiterate and literate groups.Results: Two thousand five hundred and eighteen participants completed the survey. After propensity score matching, 186 pairs of matched participants left. The overall correct rate of dementia knowledge was 70.34%. The illiterate group had a lower percentage of correct answers for each knowledge item. The item “Dementia is not a disease, it is forgetfulness due to aging” had the lowest accuracy rate in both groups (38.71% vs. 50.54%, p=0.022). Illiterate older adults were less accepting of dementia than literate older adults. The majority of participants did not agree that: “There is no need to visit a doctor when older people have memory loss, difficulty communicating, or finding words” (56.99% vs. 68.28%). Illiterate older adults had higher scores for the items assessing stigma toward dementia than literate older adults.Conclusion: Dementia-related knowledge and attitudes among community-dwelling older adults in Shanghai may be related to literacy.Keywords: knowledge, attitudes, stigma, dementia, illiterate elderly